UJI AKTIVITAS PENGHAMBATAN XANTIN OKSIDASE OLEH EKSTRAK ETANOL, PARTISI (KLOROFORM DAN METANOL) DAUN KUMIS KUCING (Orthosiphon stamineus Benth) - Yuvinda Devi Erviani Yuvinda; Wirasti; Slamet; Khusna Santika Rahmasari (Program Studi Farmasi, Universitas Muhadi Setiabudi, 2023)
Cat's Whisker Leaf (Orthosiphon stamineus Benth) is one part of the plant that can grow well in places that are exposed to a lot of sunlight. This plant contains secondary metabolites, namely flavonoids, alkaloids, saponins, steroids, and terpenoids. These compounds have the function of being able to inhibit the xanthine oxidase enzyme associated with gout. It aims to determine the effect of xanthine oxidase inhibitory activity by ethanol extract, partition (chloroform & methanol) of cat whiskers (Orthosiphon stamineus Benth) leaves. Since it is experimental study, it used xanthine oxidase inhibition reaction method by ethanol extract, partition (chloroform & methanol) whose absorbance was measured by UV-Vis spectrophotometry and compared with the positive control, namely allopurinol. The results of the xanthine oxidase inhibition test obtained in this study were ethanol extract 50 g/mL (40.22%) 100 g/mL (52.76%), methanol partition concentration of 50 g/mL (27.30%) 100 g/ mL (43.91%), chloroform partition 50 g/mL (20.66%) 100 g/mL (41.69%) and allopurinol concentration 5 g/mL (40.95%) 10 g/mL (80, 81%). Data on the inhibition of the xanthine oxidase enzyme were analyzed using One Way ANOVA with a significant value of 0.000 and continued with the Tukey test with a test value of 100 ppm methanol partitioning inhibition having the same activity as 5 ppm allopurinol. So it can be concluded that ethanol extract, chloroform partitioning and methanol partitioning of cat whiskers leaves can inhibit xanthine oxidase. Keywords: cat whiskers leaves, xantin oksidase, spektrofotometri uv-vi